CONTRIBUTION TO KNOWLEDGE OF THE GENUS SALICORNIA L. (CHENOPODIACEAE) IN ITALY - IBERITE, M. (Annali di Botanica, 1996)
The author proposes a new arrangement of the genus Salkornia L. in Italy. S. patufa Duval·Jouve, S. emerici Duval-Jouve, S. veneta Pign, et Lausi and S. dolichostachya Moss are recognized. The key of the genus, a description and original drawings for each species are given.